PENGARUH PROFITABILITAS TERHADAP PERUBAHAN LABA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Risfan Pratama; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the Effect of Profitabilitas on the profit growth of Property dan Real Estate Subsector Companies Listed on the Indonesia Stock Exchange (IDX). The ratio used to measure Profitabilitas as an independent variable is Gross Profit Margin, Nett Profit Margin, Return on Asset and Return on Equity. The method used to measure profit growth is profit. The method used to observe the effect of profitabilitas on profit growth is by using simple linear regression.The data used in this study are secondary data, namely financial statements and annual reports. The data is listed on the Indonesia Stock Exchange (IDX) for 5 years from the period 2013 to 2017. Samples were taken by purposive sampling, 7 companies were used. Data analysis used simple linear regression analysis and t test. Data analysis uses several linear regression analysis with SPSS 16. The results of the analysis show that the profitabilitas variable have a significant effect on profit growth of the Property dan Real Estate sector companies listed on the Indonesia Stock Exchange (IDX). Keywords: Profitabilitas, Profit Growth